Part A:
To solve the equation 2x^2 + 5 = 13 using inverse operations, we need to isolate the variable x.
1. Subtract 5 from both sides of the equation to get rid of the constant term:
2x^2 + 5 - 5 = 13 - 5
2x^2 = 8
2. Divide both sides of the equation by 2 to solve for x:
(2x^2) / 2 = 8 / 2
x^2 = 4
3. Take the square root of both sides of the equation to solve for x:
√(x^2) = √4
x = ±2
Therefore, the solutions for Part A are x = 2 and x = -2.
To check these solutions, substitute them back into the original equation:
When x = 2:
2(2)^2 + 5 = 13
8 + 5 = 13
13 = 13 (true)
When x = -2:
2(-2)^2 + 5 = 13
8 + 5 = 13
13 = 13 (true)
Both solutions satisfy the original equation, so they are correct.
Part B:
To solve the equation 2x^3 - 13 = 5 using inverse operations, we need to isolate the variable x.
1. Add 13 to both sides of the equation to get rid of the constant term:
2x^3 - 13 + 13 = 5 + 13
2x^3 = 18
2. Divide both sides of the equation by 2 to solve for x:
(2x^3) / 2 = 18 / 2
x^3 = 9
3. Take the cube root of both sides of the equation to solve for x:
∛(x^3) = ∛9
x = ∛9
Therefore, the solution for Part B is x = ∛9.
To check this solution, substitute it back into the original equation:
When x = ∛9:
2(∛9)^3 - 13 = 5
2(9) - 13 = 5
18 - 13 = 5
5 = 5 (true)
The solution satisfies the original equation, so it is correct.